Analisis Penerapan Risk Management Terhadap Sistem Informasi Management Perbankan - Zulhasby Assdqy Nasution; Muhammad Irwan Padli Nasution; Sri Suci Ayu Sundari (Islamic Education Journal, 2022)
The purpose of this study is to analyze risk management in management information systems. Therefore, banks and companies are advised to carry out detailed identification by looking at the hazards and risks at each stage of operation, the banking management information system workforce. The author also provides risk advice to banking institutions so that they use management in management information systems carefully and continue to pay attention and rediscover the usefulness of the risk management they use, besides that the most important thing is the development of risk management on management information systems, so as to protect all existing data on the information system. An institution or an organization that utilizes information technology to support ongoing information system activities, where the success of the services of these institutions refers to the extent to which information technology management has been implemented. The results that will be obtained from this risk management are that it will be seen that sources of threats can pose a threat to the management information system, such as human threats (hackers/crackers and insiders), as well as threats of natural disasters (floods, earthquakes, fires and others). ). The rapid development of information technology at this time requires every institution or company to always develop in all its fields, with the existence of information technology now companies can apply it as well as possible. On the other hand, the application of information technology requires investment costs that are quite expensive and can pose a significant risk of failure. When a company situation like this requires strong consistency in managing and implementing information systems. Therefore, risk management is needed by a company so that it can find out what risks can occur if implementing risk management on the banking management information system. The COBIT 4.1 framework is one of the frameworks that is often used and is very suitable for the needs of institutions and banks, because the COBIT 4.1 framework is certain to have aligned information systems with business processes, information technology resources, identified risks, carried out a risk assessment, managing risks appropriately, and being able to produce recommendations in order to achieve the desired targets.